Peningkatan Kesadaran Masyarakat Akan Pentingnya Skrining Hemoglobin dan Hematokrit Sejak Dini pada Populasi Dewasa di Gereja Asisi Jakarta - Julia Herdiman; Alexander Halim Santoso; Farell Christian Gunaidi; Jonathan Andersan; Anthon Eka Prayoga Khoto (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Anemia is a medical condition characterized by a decrease in the number of red blood cells (erythrocytes) or hemoglobin (Hb) levels in the blood which results in impaired oxygen transport to body tissues. Mild anemia is more common and is asymptomatic and does not require treatment. Anemia can have a negative impact on endurance, productivity, and is high risk during pregnancy because it can affect fetal growth and development, increase the risk of pregnancy and childbirth complications, and even maternal and child death. The Community Service (PKM) activity carried out at the Asisi Church, Tebet District aims to increase public awareness of the importance of early detection of anemia through hemoglobin and hematocrit screening activities. This activity uses the Plan-Do-Check-Act (PDCA) approach which includes capillary blood tests with Point-of-Care Testing (POCT) tools and education about symptoms, risk factors, and prevention of anemia. Of the 68 participants involved, 40 people (58.82%) were identified as having anemia, while 28 people (41.18%) had normal hemoglobin levels. These results emphasize the importance of early anemia screening to prevent long-term complications and build public awareness of the importance of maintaining optimal hemoglobin levels to support ongoing health and quality of life. Keywords: Anemia, Early Detection, Hemoglobin, Hematocrit, Screening